(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2014)
Background: This observational study done on the indoor patients of department of Physical Medicine and Rehabilitation, Chittagong Medical College Hospital, admitted during the year 2011. The objective of this study was to see the most prevalent diseases admitted in our department. Methods: Participants (225) were all the patients admitted during the period of 2011. Patients admitted more than once were recorded once only. Patients data were taken from hospital records. Results: Spondyloarthropathies (SpA) comprised 18.66% of the patients. Total patient of SpA was 42. Among them AS was 47.62%. Prolapsed lumbar disk (PLID) patients constituted 12.44% (28) of hospital admission. Twenty one (9.33%) patients suffered from other causes lumbago-sciatica. Admitted RA patient number were 12 (5.33%) during this year. Total twelve patients with bone TB (5.33%) were admitted during 2011. Nine TB patients (75% of bone TB) had TB in the hip. Total Stroke patients admitted in that year were 9 (4%). Among them 8 (88.89%) were ischemic. Conclusion: SpA, PLID and other lumbago-sciatica patients comprised the major bulk of the patients in inpatient department of PM&R. Musculoskeletal diseases were the commonest cause of hospital admission for rehabilitation. Neurological causes were next common. Inflammatory musculoskeletal diseases also formed a good number of patients. DOI: http://dx.doi.org/10.3329/cmoshmcj.v13i1.19416